The Relationship between Shyness and Motivation to Speak English of the First Year Students of English Study Program of FKIP UIR Pekanbaru - Marhamah, Marhamah (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2016)
The objectives of this research are (1) to find out if there is a relationship between shyness and motivation to speak English of the first year students of English study program of FKIP UIR Pekanbaru, (2) to know their shyness and their motivation to speak in speaking English of the first year students of English Study Program of FKIP UIR Pekanbaru, and (3) to know how the relationship between shyness and motivation to speak in speaking English of the first year students of English Study Program of FKIP UIR Pekanbaru. Shyness means a feeling about oneself in a presence of other. Motivation is process of stimulating peple to action t accomplish desired goals. In this research, motivation to speak means to stimulate students to speak English. There are two variables in this research. Shyness is taken as an independent variable and motivation to speak is taken as a dependent variable. The total population of the first year students is about 154. So, the sample of this research is 25 students. The instrument of this research is questionnaire. The aspects of students’ shyness are (1)worry about their think of them, (2) become shy to deal with people from a different social class or to work with more skilled people, and (3) avoid social gathering and usually speak in low voice. The aspect of students’ motivation to speak English are integrative and instrumental motivation. Based on the result of the analysis, there are only 40 % of the students that were indeed shy. It can be concluded that there is significant relationship between students’ shyness and their motivation t speak English.